Fire retardancy of polymers : the use of intumescence - Bras, M. Le (The Royal Society of Chemistry, 1998)
Covers the following topics: Strategies; Intumescence: Mechanism studies; New intumescent polymetric materials; Flame retarded intumescent textiles; Intumescence - an environmentally friendly process?